Antioxidant and neuroprotective effects of dexpanthenol in rats induced with traumatic brain injury - YEGEN, BERRAK (My University, 2023)
Trauma-induced primary damage is followed by secondary damage, exacerbating traumatic brain injury (TBI). Dexpanthenol has been shown to protect tissues against oxidative damage in various inflammation models. This study aimed to investigate possible antioxidant and neuroprotective effects of dexpanthenol in TBI. Wistar albino male rats were randomly assigned to control (n = 16), trauma (n = 16) and dexpanthenol (500 mg/kg; n = 14) groups. TBI was induced under anesthesia by dropping a 300 g weight from 70-cm height onto the skulls of the rats. Twenty-four hours after the trauma, the rats were decapitated and myeloperoxidase (MPO) levels, luminol- and lucigenin-enhanced chemiluminescence (CL), malondialdehyde (MDA) levels, superoxide dismutase (SOD) levels, and catalase (CAT) and caspase-3 activities were measured in brain tissues. Following transcardiac paraformaldehyde perfusion, histopathological damage was graded on hematoxylin-eosin-stained brain tissues. In the trauma group, MPO level, caspase-3 activity and luminol-lucigenin CL levels were elevated (p < 0.05–0.001) when compared to controls; meanwhile in the dexpanthenol group these increases were not seen (p < 0.05–0.001) and MDA levels were decreased (p < 0.05). Decreased SOD and CAT activities (p < 0.01) in the vehicle-treated TBI group were increased above control levels in the dexpanthenol group (p < 0.05–0.001). in the dexpanthenol group there was relatively less neuronal damage observed microscopically in the cortices after TBI. Dexpanthenol reduced oxidative damage, suppressed apoptosis by stimulating antioxidant systems and alleviated brain damage caused by TBI. Further experimental and clinical investigations are needed to confirm that dexpanthenol can be administered in the early stages of TBI.
Keywords: Antiapoptotic; Anti-inflammatory; Antioxidant; Dexpanthenol; Neuroprotection; Traumatic brain injury